2015
DOI: 10.7324/japs.2015.50926
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Endophytic Bacteria Isolated from Marine Sponge Haliclona fascigera for Inhibition against Clinical Isolates of Methicillin Resistant Staphylococcus aureus (MRSA)

Abstract: Marine endophytic bacteria are a valuable source of novel antibacterial in combating pathogenic isolates of methicillin-resistant Staphylococcus aureus (MRSA), a global nosocomial problem today. The aim of this study was to assess in vitro anti-MRSA activity of extracts from bacteria endophyte of marine sponge Haliclona fascigera collected from Setan Island, South Coast of West Sumatra, Indonesia. Anti-MRSA activity test carried out by the agar diffusion method using paper disk. The endophytic bacteria from sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…Our earlier studies showed that the endophytic fungi are a potential source of antibiotics and anticancer compounds. (Handayani et al, 2015a;Handayani et al, 2015b;Handayani et al, 2016;Harrizul et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier studies showed that the endophytic fungi are a potential source of antibiotics and anticancer compounds. (Handayani et al, 2015a;Handayani et al, 2015b;Handayani et al, 2016;Harrizul et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This value is considered quite promising. For comparison, the previous research conducted by Handayani et al (2015) shows an antagonistic activity of six strain of Bacillus sp. and four strain of Corynebacterium sp.…”
Section: Endophytic Bacteria In Seagrass With Antibacterial Activitiementioning
confidence: 92%
“…The second stage is multilevel maceration and extraction using methanol, ethyl acetate and n-hexane solvents. Phytochemical screening based on Franswort [10] and the antibacterial activity test of oil palm fronds extract based on Handayani et al [11].…”
Section: Methodsmentioning
confidence: 99%